SDN Controller for Optical Network Control - Sylwester Kaczmarek; Magdalena Mlynarczuk; Maciej Sac; Patryk Miklaszewski (IEEE Access)
The ability of centralized programming flow tables in switches and routers to perform programmable resource control and management from the central controller under the Software Defined Networking (SDN) concept has introduced a new approach to controlling and managing network resources. The main principles of the SDN concept, as defined by the Open Networking Foundation (ONF), apply primarily to packet networks, making the usage of SDN for optical networks an area of ongoing work. However, ITU-T standardization recommendations have described the reference SDN controller architecture applicable to optical transport networks in terms of abstract components provided by the Automatically Switched Optical Network (ASON) approach. The paper regards the problem of an SDN controller for optical network control according to the G.7702 ITU-T recommendation approved in 2022. The proposition of the SDN controller presented in the paper is compliant with the guidelines outlined in ITU-T recommendations, while ensuring compatibility with the standards established for OpenFlow. The integration of the SDN concept with optical network architecture is performed based on an ASON/GMPLS optical network. In the presented solution, the SDN controller is built with ASON controllers, and dedicated OpenFlow messages are proposed based on ITU-T and ONF guidelines. The proposed solution is evaluated with the simulation model in the OMNeT++ environment. The performance of the proposed solution under specific traffic conditions and different SDN controller placements is presented.